Relationship between Spirituality and Perceived Social Support with Success in Alcoholics Anonymous - Hosmane, Mala Sita (2019)
Failure in treatment and Alcoholics Anonymous (AA) leads to continued addiction, but practitioners need to learn which factors predict better outcomes in AA to make better referrals. Here, the predictive relationship between spirituality and perceived social support with success in AA was examined based on Frankl's theory on meaning in life. A quantitative, correlational design was used to determine whether there was a statistically significant predictive relationship between spirituality, as measured by the Assessment of Spirituality and Religious Sentiments, and perceived social support, as measured by the Multidimensional Scale of Perceived Social Support, with success in AA, as measured by the binomal sobriety variable with either totally sober over the last 90 days or not. Data were collected using an anonymous online and in person survey, and logistic regression was used to analyze the data on the final sample of 93. Inclusion criteria was adult age, U.S. residency, and former or current AA membership. The new model's classification table was nonsignificant without improving classification of cases as sober/nonsober. The overall model was significant per the chi-square results and the spirituality odds ratio was significant in predicting sobriety. Therefore, there was a significant predictive relationship found between spirituality and success in AA, but not for perceived social support. Recommendations include AA's value despite spirituality or social support level for recovery and spirituality as still a tool in recovery. Positive social change implications include better understanding of the factors leading to success in AA, and therefore better referrals to AA or other such adjunctive support services needed, which can improve outcomes for clients struggling with alcohol addiction